Tsar : a thriller - Bell, Ted (Bell, Ted. Alex Hawke novel., 2008)
Swashbuckling counter spy Alex Hawke is the only man, both Americans and the Brits agree, who can stop the madness created by the new Russia and its new Tsar, who is pulling strings and pulling them hard.